Comparison of efficacy and safety of the combined laser treatment technology versus conventional laser photocoagulation in diabetic macular edema management - Aleksander Victorovich Doga; Galina Fedorovna Kachalina; Elena Konstantinovna Pedanova; Dmitry Anatolievich Buryakov (Сахарный диабет, 2017)
Aim. To evaluate the efficacy and safety of the novel combined laser treatment technology compared with those of the conventional laser photocoagulation in diabetic macular oedema management. Material and methods. Fifty eyes of 44 patients with clinically significant diabetic macular oedema were enrolled. Patients of the main group (25 eyes) underwent combined laser treatment, whereas patients in the control group (25 eyes) underwent modified ETDRS (mETDRS) focal/grid photocoagulation. Results. Mean central point thickness (CPT) in the main group decreased from 411.24 ± 126 µm to 359.86 ± 120.4 µm (p < 0.05), with a subsequent increase in the mean best-corrected visual acuity (BCVA) from 0.52 ± 0.2 at baseline to 0.71 ± 0.2 (p < 0.05) at the 12-month follow-up. The mean central retinal sensitivity (RS) improved from 11.27 ± 3.8 dB to 13.24 ± 3.2 dB (p < 0.05). In the control group, our results showed similar improvement in BCVA and CPT values at the 12-month follow-up (from 0.59 ± 0.12 to 0.72 ± 0.23 and from 424.17 ± 68.12 µm to 387.51 ± 93.45 µm, respectively, p < 0.05). The RS value, on the contrary, decreased from 12.32 ± 0.90 dB to 10.14 ± 0.71 dB (p < 0.05). Conclusions. The combined laser technology is a safe treatment technique that allows to minimise the extent of laser-induced chorioretinal complex damage due to the contribution of subthreshold micropulse laser photocoagulation. The efficacy of this novel technology is comparable with that of the mETDRS technique in the resolution of macular oedema and BCVA increase. This technology also provides an advantage of RS improvement and the possibility of safe and repetitive treatment sessions.